Gaya Bahasa dalam Lirik Lagu “Epic Rap Battles of Presidency 2024” - Dahlena, Srik; Febria, Rhani (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
Hip hop music continues to evolve utilizing innovative and often rebellious language. More than just background music, hip hop song lyrics act as verbal manifestos, social commentary and poetic expression. This paper explores the intricate relationship between language style and hip hop song lyrics. The method used in this research is a qualitative method. The data source in this research is the lyrics in the song entitled